Hypertension in Non-Type 2 Diabetes in Isfahan, Iran: Incidence and Risk Factors. (20th December 2017) - Janghorbani, Mohsen; Aminorroaya, Ashraf; Amini, Masoud
Abstract : Objective. To estimate the incidence of and risk factors for the development of hypertension (HTN) in people with T1D using routinely collected data. Method. The mean 16-year incidence of HTN was measured among 1, 167 (557 men and 610 women) nonhypertensive patients with T1D from Isfahan Endocrine and Metabolism Research Center outpatient clinics, Iran. HTN was defined as a systolic blood pressure (BP) of 140 mm Hg or higher and/or a diastolic BP 90 mm Hg or higher and/or use of antihypertensive medications. The mean (standard deviation [SD]) age of participants was 20.6 years (10.5 years) with a mean (SD) duration of diabetes of 3.6 years (4.8 years) at registration. Results. The prevalence of HTN at baseline was 9.7% (95% CI: 8.2, 11.5). Among the 1, 167 patients free of HTN at registration who attended the clinic at least twice in the period 1992–2016, the incidence of HTN was 9.6 (8.0 women and 11.3 men) per 1000 person-years based on 18, 870 person-years of follow-up. Multivariate analyses showed that male gender, older age, higher triglyceride, and higher systolic BP were significantly and independently associated with the development of HTN in this population. Conclusion. These findings will help the identification of those patients with T1D at particular risk of HTN and strongly support the case for vigorous control of BP in patients with T1D.